Analisis Peran dan Tanggung Jawab Pemerintah Daerah terhadap Pasal 43 Ayat 1 Peraturan Pemerintah Republik Indonesia Nomor 27 Tahun 2014 tentang Pengelolaan Barang Mlik Negara/Daerah - Lais Batrisiya; Eti Karini; Olivia Rizka Vinanda (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The management of regional assets, particularly land assets, is a legal obligation of the regional government as stipulated in Article 43 paragraph (1) of Government Regulation Number 27 of 2014, which requires management to be carried out in an orderly, effective, efficient, transparent and accountable manner. This study aims to analyze the role and responsibilities of the Mesuji Regency Regional Government in implementing these provisions, through a study at the Regional Finance and Asset Management Agency (BPKAD). The method used is empirical legal research through interviews with relevant officials and staff. The results of the study indicate that institutionally, BPKAD has carried out the functions of administering, securing and utilizing land assets, but its implementation has not been fully optimal. There are a number of multidimensional obstacles, including uncertified land assets, overlapping ownership and limited human resources and budget. These conditions have an impact on weak legal certainty over regional assets and have the potential to cause state losses. This study concludes that the success of regional land asset management depends not only on the internal capacity of BPKAD, but also requires effective cross-agency coordination, particularly with the National Land Agency, in order to realize accountable and legally just regional asset governance.